Atomic force microscopy and scanning electron microscopy analysis of daily disposable limbal ring contact lenses. (2nd April 2014) - Lorenz, Kathrine Osborn; Kakkassery, Joseph; Boree, Danielle; Pinto, David
<x xml:space="preserve">Abstract</x> Background Limbal ring (also known as 'circle') contact lenses are becoming increasingly popular, especially in Asian markets because of their eye‐enhancing effects. The pigment particles that give the eye‐enhancing effects of these lenses can be found on the front or back surface of the contact lens or 'enclosed' within the lens matrix. The purpose of this research was to evaluate the pigment location and surface roughness of seven types of 'circle' contact lenses. Methods Scanning electron microscopic (SEM) analysis was performed using a variable pressure Hitachi S3400N instrument to discern the placement of lens pigments. Atomic force microscopy (Dimension Icon AFM from Bruker Nano) was used to determine the surface roughness of the pigmented regions of the contact lenses. Atomic force microscopic analysis was performed in fluid phase under contact mode using a Sharp Nitride Lever probe (SNL‐10) with a spring constant of 0.06 N/m. Root mean square (RMS) roughness values were analysed using a generalised linear mixed model with a log‐normal distribution. Least square means and their corresponding 95% confidence intervals were estimated for each brand, location and pigment combination. Results SEM cross‐sectional images at 500× and 2, 000× magnification showed pigment on the surface of six of the seven lens types tested. The mean depth of pigment for 1‐DAY ACUVUE DEFINE (1DAD) lenses was 8.1 μm below the surface of the lens, while the remaining lens types tested had pigment particles on the front or back surface. Results of the atomic force microscopic analysis indicated that 1DAD lenses had significantly lower root mean square roughness values in the pigmented area of the lens than the other lens types tested. Conclusions SEM and AFM analysis revealed pigment on the surface of the lens for all types tested with the exception of 1DAD. Further research is required to determine if the difference in pigment location influences on‐eye performance.